2016
DOI: 10.1038/srep29428
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of self-fertile isolates in Phytophthora infestans may attribute to their higher fitness relative to the A1 isolates

Abstract: Knowledge of population dynamics of mating types is important for better understanding pathogen’s evolutionary potential and sustainable management of natural and chemical resources such as host resistances and fungicides. In this study, 2250 Phytophthora infestans isolates sampled from 61 fields across China were assayed for spatiotemporal dynamics of mating type frequency. Self-fertile isolates dominated in ~50% of populations and all but one cropping region with an average frequency of 0.64 while no A2 isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
0
28
2
1
Order By: Relevance
“…In contrast to the findings of Zhu et al (2016), studies of the P . infestans population in northern China (Heilongjiang) over a 14‐year period (2005–2019) found that while the A1 genotype SIB‐1/JP‐2 was dominant before 2010, the frequency of 13_A2 increased from 2011 to 2013, although it was not found in 2015–2016 (M. Guo, Heilongjiang Academy of Agricultural Sciences, China, 2020, personal communication).…”
Section: Country Profilescontrasting
confidence: 89%
See 2 more Smart Citations
“…In contrast to the findings of Zhu et al (2016), studies of the P . infestans population in northern China (Heilongjiang) over a 14‐year period (2005–2019) found that while the A1 genotype SIB‐1/JP‐2 was dominant before 2010, the frequency of 13_A2 increased from 2011 to 2013, although it was not found in 2015–2016 (M. Guo, Heilongjiang Academy of Agricultural Sciences, China, 2020, personal communication).…”
Section: Country Profilescontrasting
confidence: 89%
“…Southern China (Guangxi, Guangdong, and Fujian provinces) accounts for 5% of the total area and both major hosts of P . infestans are cultivated, potatoes in the winter and tomatoes in the spring (Chen & Qu, 2008; Zhu et al, 2016). The differences in cultivation practices, together with movement of host material within the country and introduction of genotypes from external sources, impact the disease cycle as well as the population structure of P .…”
Section: Country Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytophthora infestans is considered to be a heterothallic oomycete with two mating types designated A1 and A2, despite the existence of self‐fertile isolates (Judelson, ). It can reproduce sexually, asexually, and/or parasexually (Billiard et al, ; Zhu et al, ) and has a potential for long distance wind dispersal (Granke, Windstam, Hoch, Smart, & Hausbeck, ). The pathogen has a large genome (~240 Mbp) rich in transposable elements (>75% of total genome) (Haas et al, ; Vetukuri et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The mating types of Phytophthora species, referred to as A1 and A2, do not signify the production of particular sex organs, as isolates of either mating type are hermaphroditic and thus capable of producing both antheridia and oogonia, the male and female reproductive organs, respectively (Judelson 1997). Each mating type secretes a specific hormone (a1 or a2) that induces sexual reproduction in isolates of the opposite mating type (Harutyunyan et al 2008), but the isolates of A1A2 mating type as self-fertile isolates can induced sexual reproduction with no other isolates (Zhu et al 2016). Mating type of each isolate was determined by the sputum culture method (Qi et al 2005).…”
Section: Methodsmentioning
confidence: 99%